2001
DOI: 10.1001/archotol.127.10.1230
|View full text |Cite
|
Sign up to set email alerts
|

How Do the Cervical Plexus and the Spinal Accessory Nerve Contribute to the Innervation of the Trapezius Muscle?

Abstract: Our results, especially those involving the descending part of the trapezius muscle, may help to minimize the rate of unexpected trapezius muscle paresis after surgery of the neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
52
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 21 publications
4
52
0
Order By: Relevance
“…The descending part of the trapezius was found to be mainly innervated by the spinal accessory nerve. Astonishingly enough, the transverse and ascending parts of trapezius were reported by Kierner et al [19,20] to receive their motor innervation mainly from the spinal accessory nerve, with only minor contributions from the cervical plexus. Noticeably, damage to the accessory nerve atrophies the trapezius [4,16,21].…”
Section: Discussionmentioning
confidence: 94%
“…The descending part of the trapezius was found to be mainly innervated by the spinal accessory nerve. Astonishingly enough, the transverse and ascending parts of trapezius were reported by Kierner et al [19,20] to receive their motor innervation mainly from the spinal accessory nerve, with only minor contributions from the cervical plexus. Noticeably, damage to the accessory nerve atrophies the trapezius [4,16,21].…”
Section: Discussionmentioning
confidence: 94%
“…It is well known that the cervical plexus and SAN innervate the transverse and ascending portions, but only a single branch of the SAN supplies the descending portion [13,14]. However, reports as to the segmental innervation level of the trapezius muscle, views on where the branches of the cervical plexus join the SAN in playing their role, and opinions about whether their role is independent of the SAN differ in the literature [15,16,17,18]. Moreover, whether these branches have motor fibers and whether these contributions could provide enough input to the muscle is still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, whether these branches have motor fibers and whether these contributions could provide enough input to the muscle is still uncertain. Kierner et al [15 ]reported that the SAN and the trapezius branches of the cervical plexus merge and pass together to the transverse part as well as to the ascending part of the trapezius muscle. Brodal [16 ]reported that the SAN is the main innervation to the upper and middle trapezius, whereas the C3 and C4 nerves are the main innervations to the lower trapezius.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a close relationship was demonstrated between the activities of the trapezius and the facial muscles. Of interest in this respect is that the development and innervations of the trapezius muscle is different from that of the other somatic skeletal muscles in that the trapezius muscle belongs closely to the facial muscles (Kierner et al 2001). Therefore, the motor control of this muscle may be much closer related to hand-eye coordination than being coordinated with the activity of other limb muscles; although there are still more questions than answers regarding the innervation of this muscle (DeToledo and David 2001).…”
Section: Discussionmentioning
confidence: 99%